Morfologi Dan Sifat Panas Campuran Poli Etilen Terepalat (PET) Poli Etilen Naftalat (PEN) - Wiwik Pudjiastuti (Balai Besar Kimia dan Kemasan, 1996)
Morphology and thermal properties of strand of PET and PEN blend were investigated using differential scanning calorimeter, X - ray measurement and scanning electron microscope.The PET/PEN blend had almost an amorphous phase and showed definitely a single glass transition. Temperature of the glass transition increased with increasing PEN content. In anamorphous phase, PET is able to be miscible with PEN.